2021
DOI: 10.4143/crt.2020.063
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Learning Curve on the Survival of Abdominal or Minimally Invasive Radical Hysterectomy for Early-Stage Cervical Cancer

Abstract: The objective of this study was to define the learning curve required to attain satisfactory oncologic outcomes of cervical cancer patients who were undergoing open or minimally invasive surgery for radical hysterectomy, and to analyze the correlation between the learning curve and tumor size. Materials and Methods Cervical cancer patients (stage IA-IIA) who underwent open radical hysterectomy (n=280) or minimal invasive radical hysterectomy (n=282) were retrospectively reviewed. The learning curve was evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 28 publications
(32 reference statements)
2
17
0
Order By: Relevance
“…Several studies have focused on the correlation between surgeon proficiency and clinical outcomes in recent years. Lan Ying Li et al found that compared to open surgery, more cases were required for surgeons performing minimally invasive RH to reach an acceptable five-year DFS (8). Kim et al demonstrated that surgeons' proficiency in the MIS group significantly affected progression-free survival (PFS) (9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have focused on the correlation between surgeon proficiency and clinical outcomes in recent years. Lan Ying Li et al found that compared to open surgery, more cases were required for surgeons performing minimally invasive RH to reach an acceptable five-year DFS (8). Kim et al demonstrated that surgeons' proficiency in the MIS group significantly affected progression-free survival (PFS) (9).…”
Section: Introductionmentioning
confidence: 99%
“…Lan Ying Li et al. found that compared to open surgery, more cases were required for surgeons performing minimally invasive RH to reach an acceptable five-year DFS ( 8 ). Kim et al.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing studies showed that high surgical volume of cervical cancer was a favorable prognostic factor for operative outcomes and peri-operative complication rates ( 18 21 ). Latest studies stressed that a steady trend of reduction in disease recurrence risk is associated with increased surgeon experience ( 22 , 23 ). The 3-year RFS was significantly lower at the beginning of a surgeon’s learning path compared to the time he had been adequate experience.…”
Section: Discussionmentioning
confidence: 99%
“…MIS revealed superiority of survival outcomes in prostate, colon and rectum cancers and equivalent outcomes in endometrial cancer according to the Gynecologic Oncology Group Study LAP2 trial and the laparoscopic approach to cancer of the endometrium LACE trial [18][19][20]. Researchers proposed several hypothetical factors that might lead to poor performance of MIS in cervical cancer such as uterine manipulator, CO 2 pneumoperitoneum, learning curve, hospital volume, technique of surgeons and tumor size in patients [21,22]. Therefore, we aim to evaluate the oncological safety of MIS in cervical cancer patients stratified by characteristics of disease (FIGO stage and tumor size), publication (publication time and journal), study design (singlecenter or multi-center) and treatment center (average sample size per center) and to identify possible factors that led to the controversies of MIS among previous studies.…”
Section: Introductionmentioning
confidence: 99%